Tradisi Sedekah Laut di Daerah Pesisir dalam Prespektif Hukum Islam (Studi Kasus di Desa Kebloran, Rembang) - Intan Oktaviyanti (Lakpesdam PCNU Kota Salatiga, 2024)
Indonesia, as an archipelagic country, has a wide diversity of coastal traditions that continue to thrive within local communities, one of which is the Sedekah Laut (Sea Almsgiving) tradition in Kebloran Village, Kragan District, Rembang Regency. This tradition is commonly understood as an expression of fishermen’s gratitude for safety and livelihood from marine resources; however, it also raises debate regarding the limits of customary practices within the framework of Islamic law, particularly in relation to the ritual of larung sesaji (casting offerings into the sea). This study addresses four research questions: (1) how Sedekah Laut is carried out in Kebloran Village, (2) what symbolic meanings are embedded in the tradition, (3) what socio-religious values are produced, and (4) how Sedekah Laut is positioned in the perspective of Islamic law. This research employs a qualitative approach with a field research design. Data were collected through purposive interviews with key figures and tradition participants (the hamlet head, local residents, and festival participants), supported by a literature review and documentation of the ritual sequence. Data were analyzed descriptively using thematic reduction, presentation, and conclusion drawing, by treating the tradition as a socio-cultural practice examined through key fiqh parameters especially intention (niyyah), monotheistic doctrine (tawhid), and the admissibility limits of customary practice (‘urf). The findings show that Sedekah Laut in Kebloran is performed through a series of activities including pengajian/tirakatan (religious gathering/vigil), a procession to the الساحore, and larung sesaji in the middle of the sea, accompanied by communal activities such as shared meals and entertainment. The tradition is interpreted as gratitude and a hope for safety and abundant catches, while also strengthening social cohesion. Prominent values include mutual cooperation (gotong royong), social bonding (silaturahmi), togetherness, and cultural preservation, reinforced by religious practices such as prayers and Qur’anic recitation. From the perspective of Islamic law, Sedekah Laut may be regarded as a form of specific ‘urf that is acceptable insofar as its orientation remains gratitude to Allah and social solidarity; however, it becomes problematic and prohibited if it involves beliefs that safety or sustenance are sought from entities other than Allah, as this contradicts the principle of tawhid. As a recommendation, religious and cultural guidance is needed so that the tradition can be preserved without elements that may undermine Islamic creed, for example by strengthening prayer and religious gatherings, reaffirming the intention of gratitude to Allah, and modifying symbols and practices perceived as offerings to entities other than Allah, while maintaining the social, educational, and cultural functions of Sedekah Laut.